The Identification of Polymorphisms in the Coding Region of the Apolipoprotein (a) Gene - Prins, Janke; Leus, Frank R.; Bouma, Bonno N.; van Rijn, Herman J. M. (Thrombosis and Haemostasis, 1999)
Lipoprotein (a) [Lp(a)] is a quantitative genetic trait in human plasma and elevated levels represent a major inherited risk factor for the development of atherosclerotic disease. In our search for sequence polymorphisms in the coding region of the apolipoprotein(a) [apo(a)] gene that may affect the Lp(a) concentration, four new polymorphic sites were identified. These include two coinciding polymorphisms with an allele frequency of 38% located at amino acid positions 87 and 101 (Leu87,101 →Val) in the interkringle region of kringle IV (K.IV) type 7 and two polymorphisms located in K.IV type 7 (Arg60 →Ser) and in K.IV type 10 (Tyr2 →Phe) both with estimated allele frequencies of about 1%.The linkage between the newly identified K.IV type 7 Leu87,101 →Val polymorphism and earlier described polymorphic sites in the non-coding and coding regions of the apo(a) gene, its distribution over the apo(a) isoform sizes and its possible influence on the Lp(a) concentration was analysed in 201 healthy unrelated Caucasians. The earlier described polymorphic sites included in this study were the variable number of a TTTTA pentanucleotide repeat (7-11 PNR) starting at -1231 bp, the -772 bp G/A polymorphism, the +93 bp C/T polymorphism and the +121 bp G/A polymorphism in the non-coding region, and the K.IV type 8 Thr12/Pro polymorphism and the K.IV type 10 Thr66/Met polymorphism in the coding region of the apo(a) gene.Linkage disequilibria were observed between the polymorphic sites in the 5’ non-coding region and the sites in K.IV type 7 and 8 in the coding region of the apo(a) gene, confirming that the expansion of the variable number of K.IV type 2 repeats results from intrachromosomal recombinational events. The distribution over the apo(a) isoform sizes of the K.IV type 7 Val87,101 subtype was not significantly different from that of the K.IV type 7 Leu87,101 wild-type, suggesting a relative ancient mutational event. No influence of the K.IV type 7 Leu87,101 →Val polymorphism on the Lp(a) level was observed. In fact, of all the polymorphic sites studied, only the +121 A subtype could be associated with an increased, and the K.IV type 8 Pro12 and the 10 PNR subtypes with a reduced, Lp(a) concentration corrected for apo(a) isoform size (p <0.05).
Keywords: Apolipoprotein (a); lipoprotein (a); polymorphic sites